BK polyomavirus in the urine for follow-up of kidney transplant recipients. (January 2019) - Brochot, E.; Descamps, V.; Handala, L.; Faucher, J.; Choukroun, G.; Helle, F.; Castelain, S.; François, C.; Duverlie, G.; Touzé, A.
Abstract: Objectives: After kidney transplantation, human BK polyomavirus (BKPyV) can induce a progressive disease, in three stages: viruria, viraemia, and then nephropathy after a few months of viral replication. Therapeutic intervention is recommended when BKPyV is detected in the plasma. The objective of our study was to assess urinary BKPyV nucleic acid test as a predictor for developing viraemia. Methods: We first defined a viruria threshold based on 393 time-matched urine and plasma samples collected after kidney transplantation; to validate this threshold, we followed-up a cohort of 236 kidney transplant patients. Results: A BKPyV viruria threshold of 6.71 log10 copies/mL best discriminated between plasma-positive and plasma-negative patients (sensitivity 90.9% (95% CI 86.5–95); specificity 90.3% (95% CI 86.3–94.3); area under the curve 0.953 (95% CI 0.933–0.974). In the validation cohort, the risk of developing BKPyV viraemia at 1 year was 16.5% (39/236) and rose to 90.7% (39/43) if BKPyV viruria remained above the threshold of 6.71 for more than 1 month. Conclusions: Sustained BKPyV viruria is a reliable, early marker of patients at high risk of developing BKPyV viraemia. This marker should alert the clinician early, and thus allow timely therapeutic intervention.